Measurement of forward Z → e+e− production at √s = 8 TeV - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
A measurement of the cross-section for Z-boson production in the forward region of pp collisions at 8 TeV centre-of-mass energy is presented. The measurement is based on a sample of Z → e+e− decays reconstructed using the LHCb detector, corresponding to an integrated luminosity of 2.0 fb−1. The acceptance is defined by the requirements 2.0 < η < 4.5 and pT > 20 GeV for the pseudorapidities and transverse momenta of the leptons. Their invariant mass is required to lie in the range 60-120 GeV. The cross-section is determined to be σ(pp → Z → e+e−) = 93.81 ± 0.41(stat) ± 1.48(syst) ± 1.14(lumi) pb , where the first uncertainty is statistical and the second reflects all systematic effects apart from that arising from the luminosity, which is given as the third uncertainty. Differential cross-sections are presented as functions of the Z-boson rapidity and of the angular variable φ∗, which is related to the Z-boson transverse momentum.